Stroke and peripheral embolisms in a pediatric patient with giant atrial myxoma: Case report and review of current literature. Issue 30 (July 2018) - Wu, Yin; Fu, Xian-Ming; Liao, Xiao-Bo; Zhou, Xinmin
Abstract: Rationale: Cerebral stroke with peripheral embolism due to left atrial myxoma is very rare in children. Misdiagnosis may occur because of nonspecific symptoms in the heart. Patient concerns: We present a case of a 16-year-old boy who presented with ischemic stroke and embolisms in the lower extremity, caused by a giant left atrial myxoma. Diagnoses: Left atrial myxoma. Interventions: A giant gelatinous mass was completely excised, and the histopathological findings confirmed the diagnosis of atrial myxoma. Outcomes: The temperature of the right lower extremity recovered gradually, and pulse of the right dorsalis pedis artery became palpable 10 days after the surgery. The strength of the bilateral lower extremity was level 5 at discharge. Lessons: Our case, along with the review of the literature, highlights the fact that myxomas often initially present with multiple embolisms but with few cardiac symptoms. Transthoracic echocardiography should be performed immediately to make a definitive diagnosis.